Antidepressant potential of Daidzein through modulation of endocannabinoid system by targeting fatty acid amide hydrolase - Zada, Wahid; Murtaza, Ghulam; Iqbal, Ghazala; Abbas, Ghulam; Ali Khan, Shujaat; Abdul Mannan, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In recent decades, the identification of natural compounds that modulate the endocannabinoid system by fatty acid amide hydrolase (FAAH) inhibition has provided an interesting area of research. Daidzein, which is an isoflavone, has neurobiological activities that are effective against several neurological disorders which include depression. This study aimed to investigate the FAAH inhibitory activity of Daidzein through in-silico analysis via Molecular Operating Environment software together with the in-vitro FAAH inhibitory assay. Furthermore, the anti-depressive effect of Daidzein (20 mg/kg) was examined via open field test and forced swim test in both male and female mice groups. Finally, the level of depression and stress was measured by the plasma corticosterone level. Molecular docking has shown the probable binding of Daidzein with the FAAH enzyme via its ser-ser-lys catalytic triad. Daidzein binds to the active pocket of FAAH with excellent binding energy of -64.77 Kcal/mol and binding affinity of -11.77 Kcal/ mol. The findings reported that Daidzein inhibited the FAAH enzyme with IC50 value at 1.3±0.13 µM concentration. The open field test showed that Daidzein had no significant effect on locomotory activity in both male and female groups compared to fluoxetine and Arch-5HT group. Daidzein has significantly decreased the immobility time in forced swim test, which is an indicator of an anti-depressive effect. The corticosterone level that regulates depression was significantly decreased in both male and female Daidzein-treated mice groups. This study highlighted the role of Daidzein as a therapeutic agent for depression via the inhibition of FAAH and modulation of corticosterone levels.